Pemanfaatan Artificial Intelligence Bagi Dunia Pendidikan Di Era Society 5.0: Utilization of Artificial Intelligence for the World of Education in the Era of Society 5.0 - Dara Sawitri (Computer Science and Information Technology, 2025)
The development of digital technology in the Society 5.0 era has had an impact on significant changes in various aspects of life, including education. Artificial Intelligence (AI) has become an innovative technology that plays an important role in increasing the success and effectiveness of learning. Where artificial intelligence makes it possible for individual and distance learning, digitalization of education administration, and the assessment process to become faster, objective and more efficient. The existence of artificial intelligence brings students a more participatory learning experience. For educators, artificial intelligence makes it easy to provide references and learning resources that are aligned to the individual needs of students. Artificial intelligence has a moderate role in creating a more responsive, effective and personalized learning system. However, the application of artificial intelligence for education also has challenges, especially in remote areas, such as the availability of facilities and infrastructure, data management ethics, as well as the spread of technology in the form of fast internet access and understanding digital literacy. In the Society 5.0 era, artificial intelligence technology has provided many opportunities to improve the quality of learning. With artificial intelligence, more personal methods can be applied that actively discuss and contribute based on technology. With artificial intelligence in the era of society 5.0, it is hoped that the education system will be more flexible so that it can adapt its methods and curriculum to existing needs and developments in order to create highly skilled and professional human resources.